Deep phenotyping of oxidative stress in emergency room patients reveals homoarginine as a novel predictor of sepsis severity, length of hospital stay, and length of intensive care unit stay - Ng, Mei Li; Kuan, Win Sen; Pakkiri, Leroy Sivappiragasam; Goh, Eugene Chen Howe; Wu, Lik Hang; Drum, Chester Lee (Frontiers in Medicine, 2022)
Background. We aimed to determine primary markers of oxidative stress in ED patients that predict hospital length of stay (LoS), ICU LoS, and sepsis severity. Methods. This prospective, single-centre observational study was conducted in adult patients recruited from the ED who were diagnosed with either sepsis, infection without sepsis, or non-infectious, age-matched controls. 290 patients were admitted to the hospital, and 24 patients had direct admission to the intensive care unit (ICU). A panel of 269 oxidative stress and related metabolic markers were profiled for each cohort. Clinical outcomes were direct ICU admission, hospital LoS, ICU LoS, and post-hoc, adjudicated sepsis severity scoring. Bonferroni correction was used for pairwise comparisons. Principal component regression was used for dimensionality reduction and selection of plasma metabolites associated with sepsis. Multivariable negative binomial regression was applied to predict admission, hospital, and ICU LoS. Results. Homoarginine (hArg) was the top discriminator of sepsis severity [sepsis vs. control: ROC-AUC = 0.86 (95% CI 0.81-0.91)], sepsis vs. infection: ROC-AUC = 0.73 (95% CI 0.68 - 0.78)]. The 25th percentile of hArg [odds ratio (OR) = 8.57 (95% CI 1.05-70.06)] was associated with hospital LoS [IRR = 2.54 (95% CI 1.83-3.52)] and ICU LOS [IRR = 18.73 (95% CI 4.32-81.27)]. In the prediction of outcomes, hArg had superior performance compared to Arg [hArg ROC-AUC = 0.77 (95% CI 0.67-0.88) vs. Arg ROC-AUC = 0.66 (95% CI 0.55-0.78)], and dimethylarginines [SDMA ROC-AUC 0.68 (95% CI 0.55-0.79) and ADMA ROC-AUC = 0.68 (95% CI 0.56-0.79)]. Ratio of hArg and Arg/NO metabolic markers and creatinine clearance provided modest improvements in clinical prediction. Conclusions. hArg is associated with sepsis severity and predicts hospital and ICU LoS, making it a useful biomarker in guiding treatment decisions for ED patients.